If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -1y) * dx + (2x + y) * dy = 0 Reorder the terms for easier multiplication: dx(2x + -1y) + (2x + y) * dy = 0 (2x * dx + -1y * dx) + (2x + y) * dy = 0 Reorder the terms: (-1dxy + 2dx2) + (2x + y) * dy = 0 (-1dxy + 2dx2) + (2x + y) * dy = 0 Reorder the terms for easier multiplication: -1dxy + 2dx2 + dy(2x + y) = 0 -1dxy + 2dx2 + (2x * dy + y * dy) = 0 -1dxy + 2dx2 + (2dxy + dy2) = 0 Reorder the terms: -1dxy + 2dxy + 2dx2 + dy2 = 0 Combine like terms: -1dxy + 2dxy = 1dxy 1dxy + 2dx2 + dy2 = 0 Solving 1dxy + 2dx2 + dy2 = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'd'. d(xy + 2x2 + y2) = 0Subproblem 1
Set the factor 'd' equal to zero and attempt to solve: Simplifying d = 0 Solving d = 0 Move all terms containing d to the left, all other terms to the right. Simplifying d = 0Subproblem 2
Set the factor '(xy + 2x2 + y2)' equal to zero and attempt to solve: Simplifying xy + 2x2 + y2 = 0 Solving xy + 2x2 + y2 = 0 Move all terms containing d to the left, all other terms to the right. Add '-1xy' to each side of the equation. xy + 2x2 + -1xy + y2 = 0 + -1xy Reorder the terms: xy + -1xy + 2x2 + y2 = 0 + -1xy Combine like terms: xy + -1xy = 0 0 + 2x2 + y2 = 0 + -1xy 2x2 + y2 = 0 + -1xy Remove the zero: 2x2 + y2 = -1xy Add '-2x2' to each side of the equation. 2x2 + -2x2 + y2 = -1xy + -2x2 Combine like terms: 2x2 + -2x2 = 0 0 + y2 = -1xy + -2x2 y2 = -1xy + -2x2 Add '-1y2' to each side of the equation. y2 + -1y2 = -1xy + -2x2 + -1y2 Combine like terms: y2 + -1y2 = 0 0 = -1xy + -2x2 + -1y2 Simplifying 0 = -1xy + -2x2 + -1y2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
d = {0}
| 3(2b-2)=6(1+3b) | | (2xy-y^2)dx-x^2dy=0 | | C/d=x | | .50x+.75y=20 | | -6r-29=-5(2+5r) | | 6y+1=-13 | | 11(x-6)=-11 | | r=(7+B)m | | 8x+2=5x-6 | | 11(x-6)=11 | | -4(1-4v)-v=-4-2v | | 5(x-6)=-10 | | -(3n-5)=-5n-7 | | lnx*sin^3*y*dx+x*cosy*dy=0 | | z^2+6z+20=0 | | 5a-5=6(-4a+4) | | (x-y)ydx-x^2dy=0 | | 16lw=v | | 2x^2-3xy-2y^2-2x-11y-12=0 | | 5-3x=14+2x | | 5x-3(x-5)+9(y-5)= | | x^4-9x+7=0 | | x^4-8x^3+9x^2+28x-60=0 | | -9+n=-2(-3-2n) | | 4m+9=7m+12 | | y^4+2y^2+1=0 | | 2(-5r-6)=-12-6r | | 8x+19=26 | | 4x+2=9-2x | | 4(5x+2)=-24+4x | | 3(k-3)-5=7k-(3k-2) | | f(x)=9xln(7x)-9x |